2011
DOI: 10.1016/s0027-9684(15)30362-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Supervised Exercise Trial on Exercise Adherence Among African American Men: A Pilot Study

Abstract: Objective The objective of this pilot study was to determine the effect of a supervised short-term exercise trial on exercise adherence in a sample of African American males. Methods We observed exercise adherence rates among a group of African American men in response to an exercise intervention. Exercise adherence was determined by dividing the total number of actual sessions attended by the total number of possible sessions (12 sessions). A participant was classified as an adherer if they completed 9 out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Two studies published after the HTA review was conducted were identified that did exclude normal-weight participants. However, the pilot study by Taylor et al 38 did not report any health-related outcomes, although they did report good adherence to their PA intervention. The study by Conroy et al 39 did find that those in the intervention group had a significantly greater increase in PA levels than the control group at 3 months, but this effect was not sustained at 12 months.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Two studies published after the HTA review was conducted were identified that did exclude normal-weight participants. However, the pilot study by Taylor et al 38 did not report any health-related outcomes, although they did report good adherence to their PA intervention. The study by Conroy et al 39 did find that those in the intervention group had a significantly greater increase in PA levels than the control group at 3 months, but this effect was not sustained at 12 months.…”
Section: Discussionmentioning
confidence: 92%
“…The first was a small study (n=34) conducted by Taylor et al in 2011, which recruited African American men through a prostate cancer screening program, family physicians, urologists and through media advertisements into a pilot RCT. 38 Participants were eligible if male, aged 40–70 years and African American or African descent with a BMI between 25 and 35 kg/m 2 and a sedentary lifestyle for the last 2 years. They excluded those with history of cardiovascular disease, metabolic disease, acute infection or chronic infectious disease, resting blood pressure ≥140/90 mmHg, uncontrolled diabetes and taking medications that affect heart response or orthopedic condition that may preclude participation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a limited number of studies have been conducted that exclusively recruited [25–30] or included a substantial number of [11] African American men. While the former studies resulted in positive outcomes, they were largely short term (<8 weeks), contained small sample sizes (<50 men), were uncontrolled, and only assessed cardiovascular-related variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[1024] However, these studies have been conducted in predominantly white samples and did not contain a sufficient number of African American men to conduct separate analyses. Several other exercise training studies have been conducted in exclusively African American men, [25–30] though none of these interventions measured diabetes related outcomes (i.e. glucose, insulin, HbA1c).…”
Section: Introductionmentioning
confidence: 99%